Bloodstream infection caused by enteric organisms during the first 6 months after intestinal transplant. Issue 3 (27th March 2019) - Simkins, Jacques; Morillas‐Rodriguez, Jose A.; Morris, Michele I.; Abbo, Lilian M.; Camargo, Jose F.; Selvaggi, Gennaro; Beduschi, Thiago; Tekin, Akin; Vianna, Rodrigo
Abstract: Background: Data on bloodstream infection (BSI) due to enteric organisms are scarce. Methods: This retrospective study (1/2009‐5/2017) was aimed to evaluate the incidence of BSI episodes due to enteric organisms during the first 6 months after intestinal transplant (ITx). Differences between the first (2009‐2012) and second period (2013‐2017) were evaluated as they differed from each other in the perioperative fungal prophylaxis and immunosuppressive regimen. Results: Fifty‐five adult patients were analyzed. Twenty‐eight (51%) patients developed a total of 51 episodes of BSI. Mean time from transplant to BSI was 85.5 ± 58.8 days. The most common organisms were Klebsiella pneumoniae (33%), Enterococcus spp (31%), and Candida spp (18%). Twenty‐three (45%) were multidrug resistant. The most common sources were gut translocation (35%), central line infection (20%), and intra‐abdominal abscess (14%). Biopsy‐proven rejection was associated with 16 (31%) of the BSI episodes. Patients during the first period were more likely to develop BSI (79% vs 41%, P = 0.03). There were more episodes of rejection associated with BSI in the first period (45% vs 14%, P = 0.03). The rate of reoperation into the abdominal cavity within 2 weeks after ITx was higher and the transplant hospital stay was longer among those who developed BSI ( P = 0.04 for both). Conclusions: Half of our patients developed BSI (typically during the first 3 months). Gut translocation was the most common source of BSI. Patients with rejection and/or enteritis should be monitored closely for BSI.